n = 3m + 6
n − 2m = 2
What is the solution, in the form (m, n), to the system of equations?
(−4, −6)
(−5, −9)
(2, 6)
(1, 8)
Question 2
The incorrect work of a student to solve an equation 2(y + 6) = 4y is shown below:
STEP1: 2(y + 6) = 4y
Step 2: 2y + 8 = 4y
Step 3: 2y = 8
Step 4: y = 4
Which of the following explains how to correct Step 2 and shows the correct value of y?
2 should be distributed as 2y + 12; y = 6
2 should be distributed as 2y + 12; y = 3
The equation should be y + 6 = 4y after division by 2; y = 2
The equation should be y + 6 = 4y after division by 2; y = 1
Question 3
The equation 3.3x − 6.6 = 2.7x can be transformed to form which of the following expressions?
6.0x = 6.6
0.6x = 6.6
6.0x = −6.6
0.6x = −6.6
Answer:
Part 1: The solution is (-4,-6)
Part 2: 2 should be distributed as 2y + 12; y = 6
Part 3:
Step-by-step explanation:
Part 1: Given the system of equations
→ (1)
→ (2)
Solving above two equations
Subtract 2 from 1, we get
(1) ⇒
The solution is (-4,-6)
Option 1 is correct.
Part 2: The incorrect work of a student to solve an equation 2(y + 6) = 4y
we have to choose the correct step to solve value of y
Equation: 2(y + 6) = 4y
By distributive property
2y+12=4y
2y=12 ⇒ y=6
Hence, 2 should be distributed as 2y + 12; y = 6
∴ Option 1 is correct.
Part 3: Given the equation 3.3x − 6.6 = 2.7x
we have to solve
3.3x − 6.6 = 2.7x
Subtracting 2.7x both sides
Option 2 is correct.
1) 3b + b + 6 =
2)n + 5n - 3c =
3) 12d - 2d + e =
Answer:
1) 4b +6
2) 6n - 3c
3) 10d +e
Step-by-step explanation:
Answer:
6
Step-by-step explanation:
2, 6 3/7
3, 2 8/9
4, 15 1/4
5, 9 2/3
6, 7 5/8